The Effect Of Giving Onion Dayak (Eleutherrine Americana Merr) On Blood Pressure Changes In Hypertension Patients In New Village Dusun IV Kualuh Hulu District Labuhan Batu Utara - Ekin Kurniawan; Mahyunidar Mahyunidar (Science Midwifery, 2021)
Hypertension is one of the deadliest diseases in the world as many as 1 billion people in the world or 1 in 4 adults suffer from this disease. In fact, it is estimated that the number of people with hypertension will increase to 1.6 billion by 2025. This research was conducted in Pulo Dogom Village. This study aims to determine the effect of giving Dayak onion tea on changes in blood pressure in patients with hypertension. The design of this study was quasi-experimental with a sample size of 21 using one group pre post test without control. The sampling technique is by accidental sampling. Data analysis using paired T test. The statistical test shows that the Sig value is 0.014 <0.05, then H0 is rejected and Ha is accepted.